Effects of Sowing Dates and Genotypes of Castor (Ricinus communis L.) on Seed Yield and Oil Content in the South Mediterranean Basin - Valeria Cafaro; Silvio Calcagno; Cristina Patanè; Salvatore Luciano Cosentino; Giorgio Testa (Agronomy, 2023)
To evaluate the performance of dwarf castor hybrids (‘C1012’, ‘C857’, ‘C856’), compared to a local selected genotype, in four subsequent sowing dates (SW1, SW2, SW3, SW4), a trial was conducted at the experimental farm of the University of Catania (Sicily, Italy). The length of the growing season decreased with the increase of the sowing date in the average genotypes from 160 to 94 days, respectively, for the first and the last sowing date. According to the RED—Renewable Energy Directive, the genotype ‘C856’ was the earliest (112 days), resulting in suitability as a catch crop for biomass production. The results showed that early spring sowings negatively impact dwarf hybrid production (1.2 and 1.5 Mg ha−1 in SW1 and SW2, in the average of the three hybrids), which reached the highest yield in the third sowing date (2.0 Mg ha−1), preferring warmer temperatures for the germination of seeds. On the contrary, the ‘Local’ genotype reached the highest yield (1.6 Mg ha−1) in the first sowing date and linearly decreased in the subsequent ones. Nonetheless, the third sowing date positively influenced the oil content and the oil yield in all dwarf genotypes except the ‘Local’ genotype, which showed the highest oil yield in the first sowing date.